Advances in Autism: a bibliometric analysis - Mehereen Chowdhury; Murdoc Gould; Latha Ganti (Health Psychology Research)
This paper provides a comprehensive overview of AI treatment research for Autism Spectrum Disorder (ASD) from 2007 to 2023, focusing on global contributions across countries, institutions, authors, and keywords. The United States leads with 164 documents and 4988 citations, highlighting its central role in advancing AI technologies for ASD therapies, followed by significant contributions from China (90 documents, 1190 citations) and India (65 documents, 564 citations). Institutions like Stanford University and McGill University demonstrate substantial research output, while authors such as Dennis Wall are prominent with contributions that make diagnosing Autism much more efficient with the use of AI. Keywords like "Machine learning", "Autism spectrum disorder", and “Children” dominate, reflecting ongoing efforts to leverage technology for ASD interventions. Overall, this analysis underscores a dynamic global effort to enhance ASD treatment methodologies through collaborative research and technological innovations.